Intercultural learning in diverse schools: obstacles, opportunities, and outlooks - Thor-André Skrefsrud (Problemy Wczesnej Edukacji)
The emergence in recent years of the concept of intercultural learning has raised questions about how the notion relates to a pedagogy that fosters openness, exploration, and critical thinking. In this article, the author provides a critical examination of a conventional understanding of intercultural learning to clarify its construction and to elucidate its instructional implications. Central to this alternative is a pedagogy that acknowledges students’ former experiences and competencies without making cultural predictions. Instead of reducing the process of understanding to a technical issue, this paper advocates the integration of intercultural learning in schools by connecting the curriculum to students’ lives and identities. This paper ends with a consideration of the future prospects of intercultural learning, suggesting more research on how intercultural learning actually takes place in schools and society.